2009
DOI: 10.1111/j.1467-8500.2009.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Narrative Disclosures by Local Governments: A Comparative Analysis of the Textual Complexity of Mayoral and Chairpersons’ Letters in Annual Reports

Abstract: Research on local government annual reports has been limited, particularly in relation to report narratives. This study aims to determine whether characteristics of narratives vary between the reports of local governments and listed companies. After considering the nature of the potential report audiences it was predicted that, if writers consider their audience, local government report narratives would be easier to read, less likely to be obfuscated, and use fewer passive sentences than those in corporate rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Second, they use “quantitative information, narratives, photographs and graphs…to inform shareholders, creditors and others about a company’s business history, its present financial status, and its expected direction” (Courtis, 1995, p. 4). Third, annual reports are an instrument for managers to demonstrate their effectiveness (Clarke, Hrasky, & Tan, 2009, p. 197). Fourth, they help to shape the future by providing solid information about economic dynamics as a basis for investment decisions (C.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, they use “quantitative information, narratives, photographs and graphs…to inform shareholders, creditors and others about a company’s business history, its present financial status, and its expected direction” (Courtis, 1995, p. 4). Third, annual reports are an instrument for managers to demonstrate their effectiveness (Clarke, Hrasky, & Tan, 2009, p. 197). Fourth, they help to shape the future by providing solid information about economic dynamics as a basis for investment decisions (C.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that these reports were difficult to read, with Flesch Index scores between 25.2 and 43.8, thus demanding a reading ability higher than normally expected of the general population. Another study of the mayor's letters issued by Australian local governments in their annual reports found the mayor's letters also difficult to read (Clarke, Hrasky, and Tan ). In the United State local government context, Lutz et al () and Marsh et al () examined the readability of the MD&A using the Flesch‐Kincaid grade level formula.…”
Section: Resultsmentioning
confidence: 99%
“…A further contribution of this research relates to the broadening of understandings of historical public sector annual reporting practices. Previous studies have focused on contemporary practices and/or the general effects of reforms on reporting practices within public sector settings in Australia (see Cameron and Guthrie, 1993; Christensen and Skærbæk, 2007; Clarke et al, 2009; Ryan et al, 2002a). 5 While Davis and Bisman (2015) provided some insights into the annual reporting practices of the DSS, they only examined one AR from each decade between the 1940s and 1990s.…”
Section: Introductionmentioning
confidence: 99%
“… 5. Ryan et al (2002b) and Clarke et al (2009) found shortcomings in local government annual reporting in the areas of timeliness and readability. Ryan et al (2002b) did, however, report that quality of disclosures improved over time. …”
mentioning
confidence: 99%